Implementation of a PI-Controlled Closed-Loop System for Mecanum Wheel Coordination in an Omni-Directional Robot (Universitas Muhammadiyah Yogyakarta, 2023)
The MR CRUSH robot is designed for participation in the 2023 Indonesian Thematic Robot Contest (KRTMI). In the motor part of the MR CRUSH robot, each wheel is designed to rotate independently and using a mecanum wheel system. Mecanum wheels are a type of wheel that has the ability to move in all directions by combining rotational speed and direction. To maximize this capability, the force generated on each mecanum wheel must be the same as set point. One of the influences of the amount of force produced is the mecanum wheel rotation speed. This research aims to implement a closed-loop control system with a Proportional-Integral (PI) controller. By implementing this PI controller, it ensures that the rotation speed of the dc motor corresponds to the set point value given, so that the four dc motors that drive the mecanum wheel will have the same rotation speed. The parameters for the PI controller used in this research are Kp = 0.3 and Ki = 0.08. Based on the results, the closed-loop control system with the designed PI controller produces constant motor rotation speed at the set point with 0 steady-state error.